Ulinastatin Inhibits the Proliferation, Invasion and Phenotypic Switching of PDGF-BB-Induced VSMCs via Akt/eNOS/NO/cGMP Signaling Pathway - Huang C; Huang W; Wang R; He Y (Dove Medical Press, 2020)
Cheng Huang, Weihui Huang, Rui Wang, Yongli He Department of Cardiology, Guangdong Cardiovascular Institute, Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Academy of Medical Sciences, Guangzhou, Guangdong 510055, People’s Republic of ChinaCorrespondence: Cheng HuangGuangdong Cardiovascular Institute, Guangdong Provincial Key Laboratory of Coronary Heart Disease Prevention, Guangdong Academy of Medical Sciences, Dongchuan Road, 96#, Guangzhou, Guangdong 510055, People’s Republic of ChinaEmail huangcheng099@126.comBackground: Atherosclerosis is a chronic inflammatory disease responsible for thrombosis, blood supply disorders, myocardial infarction and strokes, eventually leading to increased deaths and reduced quality of life. As inflammation plays a vital role in the development of this disease, the present study aims to investigate whether urinary trypsin inhibitor (UTI) with anti-inflammatory property can inhibit the proliferation, invasion and phenotypic switching of PDGF-BB-induced vascular smooth muscle cells (VSMCs) and probe its potential mechanism.Methods: Western blot was used to detect the expressions of the proteins related to the Akt/eNOS/NO/cGMP signaling pathway, phenotypic switching and proliferation. CCK-8 assay and EdU staining were used to detect cell proliferation of VSMCs. Transwell and wound healing assays were respectively conducted to measure the invasion and migration of VSMCs. The concentration of NO was evaluated by NO detection kit. ELISA assay analyzed the expression of cyclic GMP (cGMP).Results: The expressions of p-Akt and p-eNOS were elevated by UTI treatment. Furthermore, UTI inhibited the proliferation, migration and invasion of VSMCs. UTI also increased the expressions of proteins related to phenotypic switching. The amount of NO and expression of cGMP were both elevated under UTI treatment.Conclusion: UTI inhibits the proliferation, invasion and phenotypic switching of PDGF-BB-induced VSMCs via Akt/eNOS/NO/cGMP signaling pathway, which might provide a theoretical basis for the UTI treatment of atherosclerosis.Keywords: ulinastatin, atherosclerosis, proliferation, invasion, phenotypic switching, Akt/eNOS/NO/cGMP signaling pathway